Mechanism of Metformin on LPS-Induced Bacterial Myocarditis. Issue 2 (20th May 2019) - Li, Minghua; Gou, Yawei; Yu, Hongmei; Ji, Tiefeng; Li, Yi; Qin, Ling; Sun, Wei
Aims: Metformin is commonly used to treat type 2 diabetes mellitus; however, in recent years, it was found to play a potential role in the protection of myocardial injury. In this study, we intended to investigate whether metformin had protective effects on bacterial myocarditis. Methods and Results: We stimulated rat cardiac myoblast H9c2 cells with lipopolysaccharide (LPS) and administrated with metformin. The results showed that cell viability after LPS stimulation was greatly reduced. The expression levels of phosphorylated p38 mitogen-activated protein kinases (MAPK) and c-Jun N-terminal kinases (JNK), nuclear factor (NF)-κB (NF-κB), BAX, and cleaved Caspase3 were significantly increased, while the expression of antiapoptotic protein Bcl-2 showed a prominent decrease compared to control. Nevertheless, the cells activity increased remarkably after metformin administration, and the expression levels of intracellular related proteins showed the opposite trend to that of the LPS group. Conclusion: We demonstrate that LPS stimulation may activate intracellular MAPK/JNK and NF-κB signaling pathways and thus induce cell apoptosis. In contrast, metformin reduced apoptosis by inhibiting this signaling pathway and increasing the expression level of Bcl-2. Moreover, it was found that metformin could enhance the ability of cells to antagonize redox damage by regulating the activities of superoxide dismutase and lactate dehydrogenase and subsequently promote the recovery of cardiomyocyte function.